Cancer medicines in Asia and Asia-Pacific: What is available, and is it effective enough? - Alexandru Eniu (2019)
© Author (s) or their employer(s) 2019. This review article is an overview of the session at the European Society for Medical Oncology (ESMO) Asia 2018 Congress entitled: 'Cancer medicines in Asia and Asia-Pacific: What is available, and is it effective enough?'. The article provides an overview of the session speakers' views on the impact that the lack of accessibility and availability of medicines has on patient outcomes in the treatment of breast cancer, colorectal cancer and lung cancer, responsible for more than one-third of cancer deaths in the Asian region. It also lists the various global policy initiatives that ESMO supports to promote the best cancer care in the Asian and Asia-Pacific region. The review presents extrapolated data from the 'ESMO International Consortium Study on the availability, out-of-pocket costs and accessibility of antineoplastic medicines in countries outside of Europe', which reveals several disparities among Asian countries, across the different income levels. In low- and middle-income countries, some barriers to the accessibility of anticancer medicines include the lack of government reimbursement, budget allocation for healthcare and quality-assured generic and biosimilar medicines, as well as shortages and patent rights. Throughout the article, the session presenters provide their views on strategies that can be considered to overcome these barriers.